From sustainability to resilience: tracing the transition path for spatial planning policy in Greece - Asprogerakas, Evangelos; Tasopoulou, Anastasia (European Spatial Research and Policy, 2024)
Sustainability and resilience are currently key analytical concepts with wide acceptance among different disciplines. This study initially attempts a comprehensive analysis of the current policy to specify the meaningful elements for integrating these concepts into spatial planning theory and practice. Then, a critical review of the Greek spatial planning policy aims to shed light on its evolution in relation to the two paradigms. The findings show that the actual shift from sustainability to resilience remains to be observed and that more attention should be focused on the political rather than the administrative aspect of planning.